Self-Acceptance in Breast Cancer Patients Undergoing Chemotherapy in an Integrated Cancer Installation Room In General Hospital - Nurliani, Ni Kadek Erni; Dewi, Ni Luh Putu Thrisna; Wati, Ni Made Nopita (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2025)
Abstract Chemotherapy is one of the treatments for breast cancer patients that affects the physical, psychological, and quality of life of the patient. Patients need to have a good coping mechanism to maintain a good quality of life. Several factors that affect the quality of life of cancer patients include self-acceptance. This study aims to describe the picture of self-acceptance in breast cancer patients undergoing chemotherapy. The design of this study used quantitative descriptive with a cross-sectional design. The study was conducted at the Integrated Cancer Installation of the Regional General Hospital with a sample of 149 people using a purposive sampling technique. Based on the results of the study, it was found that breast cancer patients undergoing chemotherapy experienced moderate self-acceptance as many as 72 samples (48.3%), with the largest age range of 46-55 years (54; 36.2%), most respondents were married (148; 99.3%). most respondents were in stage III (83; 55.7%), had been diagnosed with cancer for 3-6 months (54; 36.2) and were undergoing 2-3 series of chemotherapy (54: 36.3%). The higher a person's self-acceptance, the more optimistic they are in undergoing treatment for their recovery. It is expected that nurses will use a caring approach to increase patient self-acceptance during chemotherapy and provide support to patients to remain optimistic during treatment.